1 Answer | Add Yours
`(y^3-64)/(3y^2 -17y +20)`
First we will factor the numerator and denominator.
==> We know that `(a^3-b^3)= (a-b)(a^2+ab+b^2) `
`==gt (y^3-64)= (y-4)(y^2 +4y +16)`
`` ==> Now we will factor the denominator.
`==gt 3y^2 -17y +20= (3y-5)(y-4).`
`` Now we will substitute.
==> `(y^3-64)/(3y^2-17y+20)= ((y-4)(y^2+4y+16))/((3y-5)(y-4))`
`` Now we will reduce (`y-4` ).
==> `(y^3-64)/(3y^2-17y+20)= (y^2+4y+16)/(3y-5).`
We’ve answered 319,203 questions. We can answer yours, too.Ask a question